INCREASING STUDENTS INTEREST IN MATHEMATICS LEARNING USING PEER TUTOR METHOD - Fa'iq Irsyad; Anggit Prabowo (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
Interest is one of the affective aspects affecting student's achievement. This study aims to increase students' interest in learning mathematics in class VIII E students of State Junior High School (SMP N) 2 Sanden,Â Bantul Regency using peer tutor methods. The type of this research is Classroom Action Research (CAR). This study's subjects were 28 students of class VIII E SMP N 2 Sanden, Bantul Regency. The object of this study was learning using peer tutor methods. Data collection techniques used observation and questionnaire methods. Data collection instruments were observation sheets, questionnaires, and documentation. The data collected was analyzed by qualitative descriptive. This study indicates that mathematics learning with peer tutor methods can increase students' interest in learning mathematics for students of class VIII E of SMP N 2 Sanden. This is indicated by increasing students' interest in learning mathematics from cycle I to cycle II. In the first cycle, students' average score in learning mathematics is 62.23 with fewer categories. In cycle II the average score of students' interest in learning mathematics increase to 71.88 in the high category.Â